Genome Editing Redefines Precision Medicine in the Cardiovascular Field. (14th March 2018) - Dzilic, Elda; Lahm, Harald; Dreßen, Martina; Deutsch, Marcus-André; Lange, Rüdiger; Wu, Sean M.; Krane, Markus; Doppler, Stefanie A.
Abstract : Genome editing is a powerful tool to study the function of specific genes and proteins important for development or disease. Recent technologies, especially CRISPR/Cas9 which is characterized by convenient handling and high precision, revolutionized the field of genome editing. Such tools have enormous potential for basic science as well as for regenerative medicine. Nevertheless, there are still several hurdles that have to be overcome, but patient-tailored therapies, termed precision medicine, seem to be within reach. In this review, we focus on the achievements and limitations of genome editing in the cardiovascular field. We explore different areas of cardiac research and highlight the most important developments: (1) the potential of genome editing in human pluripotent stem cells in basic research for disease modelling, drug screening, or reprogramming approaches and (2) the potential and remaining challenges of genome editing for regenerative therapies. Finally, we discuss social and ethical implications of these new technologies.